2008
DOI: 10.1007/s11568-009-9032-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics education in British medical schools

Abstract: Pharmacogenetic tests allow medications to be tailored to individual patients to improve efficacy and reduce drug toxicity. In 2005, the International Society of Pharmacogenomics (ISP) made recommendations for undergraduate medical teaching in pharmacogenetics. We aimed to establish the quantity and scope of this in British medical schools. An electronic survey was sent to all British medical schools. Nineteen out of 34 (56%) medical schools responded. Sixteen of the 19 (84%) respondents provided pharmacogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 11 publications
5
23
0
Order By: Relevance
“…Based on the ISP recommendations for undergraduate medical teaching of pharmacogenetics, most British medical schools now teach pharmacogenetics for 1-2 hours. 15 Data from this survey suggests 4 hours to 8 hours of teaching pharmacogenetics be incorporated into the curricula of medical and pharmacy schools in Ghana. This can be done at the stage when the students are already familiar with basic principles of pharmacokinetics, pharmacodynamics and have completed their basic training in human genetics.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Based on the ISP recommendations for undergraduate medical teaching of pharmacogenetics, most British medical schools now teach pharmacogenetics for 1-2 hours. 15 Data from this survey suggests 4 hours to 8 hours of teaching pharmacogenetics be incorporated into the curricula of medical and pharmacy schools in Ghana. This can be done at the stage when the students are already familiar with basic principles of pharmacokinetics, pharmacodynamics and have completed their basic training in human genetics.…”
Section: Discussionmentioning
confidence: 95%
“…Insufficient education of health professionals and the lack of adequate patient education have been observed as major barriers to pharmacogenetics being integrated into clinical practice. 15 This descriptive survey assessed knowledge of pharmacogenetics among health professionals and faculty members of health training institutions. The survey showed that majority of the professionals interviewed have heard about pharmacogenetics and view it as clinically relevant to their various areas of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with the survey of laboratories providing somatic pharmacogenomic testing, perhaps reflecting an increased awareness and acceptance of genetic tests by hematologists and oncologists (Wordsworth et al, 2008), and highlights the need for a good medical education in pharmacogenetics, which is not generally seen as a priority at present (Gurwitz et al, 2005;Higgs et al, 2009). In the United Kingdom, resources are being developed to provide information to both healthcare professionals, through the NHS National Genetics Education (www.geneticseducation.nhs .uk) and Development Centre, and patients, via Labtests online (www.labtestsonline.org.uk=understanding=features= pharmacogenomics-3.html), about pharmacogenetics.…”
Section: Gardiner and Beggmentioning
confidence: 91%
“…By 2002, the American Association of Colleges of Pharmacy (AACP) had made specific recommendations for the pharmacogenomics training of students [1][2][3]. In 2005, the International Society of Pharmacogenomics (ISP) addressed their guidelines for the pharmacogenomics education of health professionals to the deans of the schools of pharmacy, medicine, and nursing [4,5]. The American College of Clinical Pharmacy (ACCP) outlined the necessary educational foundation required for pharmacists to practice personalized medicine in its 2007-2012 Strategic Plan [6].…”
Section: Pharmacists' Pharmacogenomics Edu-cation and Knowledgementioning
confidence: 99%